Harmonia Macrocosmica: Andreas Cellarius, 1596-1665 (Part I) - M.Phil. in Reformation and Enlightnement Studies (Trinity College Dublin, 2007)
The publication of Andreas Cellarius's Harmonia Macrocosmica in 1660 represented the completion of an ambitious cartographic project begun over twenty years earlier by the family of Johannes Jansonnius. Jansonnius had proposed to include in his multi-volume Novus Atlas a description of the whole world, that is 'the Heavens and the Earth'. The series incorporated the famous Blaeu Atlas. Cellarius used elaborate illustrations to depict not only the Copernican 'world system' (model of the universe), but also the classical inheritance, Ptolemy's geocentric model. The work became extremely popular and was frequently reprinted.
Exhibited at the second Glucksman Memorial Symposium on June 13th 2007
Keywords: Andreas Cellarius; Early modern cosmology; Harmonia Macrocosmica